Designing professional sports contracts from the perspective of the administrative bodies of football clubs - Abbas, Asst.Prof.Dr.Ali Salman; Musa, Asst.Prof.Dr.Mustafa Bahr (Sulaimani Journal for Humanities, 2025)
This research aims to design professional sports contracts from the perspective of the administrative bodies of football clubs by identifying (the objectives of designing professional sports contracts, the basic requirements in the clauses of professional sports contracts). The researcher used the descriptive method, as it is suitable for the nature of the research, and a random sample of (100) individuals working in the administrative bodies of football clubs in Iraq was selected. The researcher designed a questionnaire to collect the data. Among the most important conclusions were that the objectives of designing professional sports contracts are (ensuring the financial and administrative stability of the club, ensuring that the club is not exposed to legal problems due to the player's breach of contract or his transfer to another club without compensation, and establishing a clear framework for the relationship between the club and the player to avoid any misunderstandings or disputes). Among the most important recommendations was the necessity of ensuring that the contract conforms to the laws of the Court of Arbitration for Sport (CAS) in case of disputes, and avoiding ambiguous or loose phrases that may lead to multiple interpretations.
Keywords: Sports contracts; administrative bodies